(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This paper explores the viability of Tera (Nymalti) language and culture in North-Eastern Nigeria and its tendency to be endangered. Tera (Nymalti) has about more than 101,000 native speakers yet UNESCO classifies it as one of the threatened language that stands the risk of possible extinction by the end of the 21st century. In order to effectively view this assertion, questionnaires were administered in 15 districts out of the 33 districts in Tera land. The data collected were analyzed by using simple percentage method to clarify the issue. The results of the findings revealed that Tera (Nymalti) language and culture is really facing the challenges of extinction. It was recommended that parents and traditional rulers who are the custodian of the Tera (Nymalti) language and culture should adopt the use of the language in homes and palaces.